ROS-Based Multi-Robot System Simulator - Ma, Zhengguang; Zhu, Lin; Wang, Peng; Zhao, Yongguo (Chinese Automation Congress (Online), 2019)
Recently, modelling, simulation and control of coordination behavior has become an important subject in the field of complex system science. For the seamless transition between simulation, semi-physical simulation and full hardware experimentation of coordination behavior, an efficient simulator based on Robot Operating System(ROS) and Qt are provided in this paper. ROS and Qt are both powerful tools which can be used in the field of robotics and Graphical User Interface (GUI) development. The ROS-based simulator can be used to verify the coordination protocols of multi-robot system(MRS). The simulator runs under the ROS framework can both simulate and control the real robots with minor modification, therefore, the ROS-based MRS simulator is much more efficient for theoretical verification of coordination protocols of MRS.